A study for optimum productivity yield in 0.16Î¼m mixed of wafer fabrication facility - Mohd Azizi, Chik; Ve, Chun Yung; Balakrishna, Puvaneswaran; Uda, Hashim, Prof. Dr.; Ibrahim, Ahmad; Bashir, Mohamad (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/